The Effectiveness of the Project-Based Learning Model in Enhancing 21st Century Competencies of Creative Thinking in Eighth-Grade Students on National Identity and Culture at SMP Negeri 1 Kebasen - Intan Wahyu Oktaviani; Efi Miftah Faridli; Wildan Nurul Fajar (Proceedings Series on Social Sciences & Humanities, 2024)
This study aims to determine the effectiveness of the Project-Based Learning (PBL) model in enhancing 21st-century creative thinking competencies on National Identity and Culture. The research used a quasi-experimental method with a nonequivalent control group design. The sample consists of Grade VIII A as the experimental group and Grade VIII B as the control group. Data collection techniques used tests, questionnaires, observations, and documentation. The data were analyzed using paired sample tests and independent sample t-tests, indicating a result of 0.000 (p 0.05); the Project-Based Learning model effectively enhances students' creative thinking. This is further evidenced by the N-Gain test results, with the experimental group achieving 57% in the moderately effective category and the control group achieving 20% in the ineffective category. Additionally, the effect size test results show a value of 4.456663, which falls into the very high category.